Influence of 6ppd on thermal aging and ionic conductivity of mg30 polymer electrolytes - Aziz, Ahmad Fairoz; Badrudin, Fadlul Wafi; Hussin, Nur Hafiz; Ali, Ab Malik Marwan (GADING Journal of Science and Technology, 2024)
This study investigates the influence of N-1,3-dimethylbutyl-N’-phenyl-p-phenylenediamine (6PPD) in retarding the thermal ageing of methyl-grafted natural rubber (MG30) polymer electrolytes (PEs). Like other rubber derivative products, MG30 is susceptible to thermal degradation due to elevated temperatures, which in turn causes physical ageing. This deterioration has an adverse effect on both the mechanical properties and the ionic conductivity of the electrolyte. In this work, MG30 PEs were subjected to thermal degradation at 100 °C for several days, and the ionic conductivity was observed. Impedance spectroscopy was used to analyse the temperature-dependent ionic conductivity of MG30-LiTf and MG30-6PPD-LiTf PEs. The results showed that the ionic conductivity increased as the temperature increased, following the Vogel-Tamman-Fulcher (VTF) model. Further exposing the electrolytes to heat treatment at a precise temperature of 100 °C for several days led to a progressive decline in the conductivity of ions over time, likely due to the phenomenon of physical ageing. The MG30-6PPD electrolytes exhibited longer conductivity relaxation, indicating greater resilience to physical aging compared to MG30 PEs. The findings provide crucial insights into the thermal durability and potential applications of these polymer electrolytes in electrochemical devices.